It's more about a lesson than a domain: Lesson-specific autonomy support, motivation, and engagement in math and a second language. (February 2022) - Flunger, Barbara; Hollmann, Lissa; Hornstra, Lisette; Murayama, Kou
Abstract: Expanding research on the relative impact of different autonomy-supportive strategies employed by teachers across domains, the present study investigated the variation in 4 lesson-specific autonomy-supportive strategies (providing choices, rationales, accepting frustration, and stimulating interests) and 6 aspects of students' motivation and engagement in 2 domains with a repeated measurement design. For 3 weeks, 202 Dutch students from 8 eighth grade classes and 1 ninth-grade class and 12 teachers completed lesson-specific measures at the end of Math and German lessons. Students' perceptions of teachers' autonomy support and their motivation and engagement varied considerably across lessons within a domain (variance at the within-student level ranged from 19% to 51%). In random intercept-random slope models, we found that all autonomy-supportive strategies showed meaningful associations with aspects of students' motivation and engagement. We did not find substantial domain-dependency in the associations between autonomy support and the outcomes. Highlights: Distinct autonomy-supportive strategies predict students' motivation and engagement. No substantial domain-dependency in the predictions of autonomy support. Between-student differences in the effects of autonomy support on student outcomes.